People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Technical Note-Financial Safety Net and Crisis Management Arrangements. (IMF Staff Country Reports; Country Report ;, 2021)
Hong Kong SAR has significantly strengthened its crisis management arrangements through a thorough update of the framework for resolution of financial institutions, as recommended by the 2014 Financial Sector Assessment Program. The 2017 Financial Institutions (Resolution) Ordinance (FIRO) creates a resolution regime that is clear, comprehensive in scope, and closely aligned with the Financial Stability Board (FSB) Key Attributes of Effective Resolution Regimes for Financial Institutions. Some aspects of the FIRO, such as the cross-sectoral scope of the regime, are particularly strong. To implement the regime, the Hong Kong Monetary Authority (HKMA) 2 has established a Resolution Office (RO) with clear operational separation from banking supervision.